An ecological pope challenges the Anthropocene Epoch - Rolston, Holmes, 1932-2025, author; Process Century Press, publisher (Colorado State University. Libraries, 2015)
In his recent encyclical Laudatio si', On Care for our Common Home, Pope Francis is a biocentric holist, advocating "integral ecology." He fully recognizes that humans need nature as natural resources, but he limits such use with a recognition of intrinsic value in God's created order. He laments biodiversity losses, celebrating all creatures great and small. He is scientifically informed, and in result asks for a transformed world view, limiting excessive technology and taming rapacious capitalism, simultaneously conserving nature and opening up opportunity for impoverished peoples. The encyclical is about environment and equally a socio-economic critique. Those concerned with environmental ethics can welcome a new and powerful voice for saving the Earth.
Keywords: Pope Francis; Laudatio si'; St. Francis; creation; environment; conservation; intrinsic value; environmental justice; limits to growth; Anthropocene Epoch